OP0137 EFFICACY AND SAFETY OF TELITACICEPT, A NOVEL BLYS/APRIL DUAL INHIBITOR, IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS: A PHASE 3, RANDOMIZED, PLACEBO-CONTROLLED 52-WEEK STUDY - Wang, L.; Li, J.; Xu, D.; Fang, J.; Van Vollenhoven, R.; Zhang, F. (Annals of the rheumatic diseases, 2023)
BackgroundTelitacicept (TACI-Fc fusion protein) is a novel BLyS (B-lymphocyte stimulator)/APRIL (a proliferation-inducing ligand) dual inhibitor, which has been approved in 2021 in China for the treatment of patients with active systemic lupus erythematosus (SLE)[1].ObjectivesAssess the efficacy and safety of telitacicept in SLE patients in a double-blind, randomized, placebo-controlled, phase 3 trial.MethodsIn this study, 335 active SLE patients who were receiving stable standard therapy with positive ANA/anti-dsDNA and a SELENA-SLEDAI score ≥8 were randomized 1:1 to receive telitacicept 160 mg (N=167) or placebo (N=168) subcutaneously weekly for 52 weeks. The primary endpoint was the response rate of SLE responder index 4 (SRI4) at Week 52. Key secondary endpoints included: SELENA-SLEDAI, PGA, immunological biomarkers including C3, C4, IgM, IgG, IgA and CD19+ B cells. Safety was assessed during the study.ResultsBaseline demographics and disease characteristics were comparable between the two groups. The primary endpoint at Week 52 was met, with significantly greater proportion of patients in telitacicept 160 mg group vs placebo group achieving SRI4 response (Table 1). SRI4 response was sustained in telitacicept 160 mg group up to Week 52 (Figure 1A). Significantly greater proportions of subjects in telitacicept 160 mg group had improvement in SELENA-SLEDAI and PGA (Table 1 & Figure 1B, 1C). Rapid and sustained increase of C3 and C4 (Figure 1G, 1H), and reduction of IgM, IgG, IgA and CD19+ B cells (Figure 1D, 1E, 1F, 1I) were observed following telitacicept treatment. Incidences of TEAEs and infections were comparable between the two groups. Most of TEAEs were mild to moderate in severity. A greater proportion of patients receiving placebo had SAEs and serious infections compared with telitacicept 160 mg. (Table 1).Figure 1.SRI4 Response Rate (A), rate of subjects with improvement in SELENA-SLEDAI (B) and PGA (C) at each visit. Percent (%) change from baseline in IgM (D), IgG (E), IgA (F), C3 (G), C4 (H) and CD19+ B cells (I).#P<0.001 vs. Placebo; *P<0.01 vs. Placebo; +P<0.05 vs. Placebo.Table 1.Key efficacy and safety data.Efficacy, FASPlacebo (N=168)Telitacicept 160 mg (N=167)Primary endpointSRI-4 Response at Week 52 (MI), n(%)64(38.1%)138(82.6%)#SRI-4 Response at Week 52 (NRI), n(%)55(32.7%)112(67.1%)#SRI-4 Response at Week 52 (LOCF), n(%)63(37.5%)138(82.6%)#Secondary endpoints$≥4-point reduction in SELENA SLEDAI at Week 52, n(%)68(40.5%)117(70.1%)#≥0.3-point reduction in PGA at Week 52, n(%)94(56%)141(84.4%)#Severe SFI flare, Mean±SD0.6±0.890.1±0.44#Safety, SSPlacebo (N=168)Telitacicept 160 mg (N=167)TEAE, n(%)142(84.5%)153(91.6%)SAE, n(%)24(14.3%)12(7.2%)Infections and infestations+ (SOC), n(%)101(60.1%)109(65.3%)Upper respiratory tract infections, n(%)55(32.7%)71(42.5%)Urinary tract infection, n(%)26(15.5%)19(11.4%)Nasopharyngitis, n(%)11(6.5%)4(2.4%)Herpes zoster, n(%)6(3.6%)8(4.8%)Gastroenteritis, n(%)5(3.0%)9(5.4%)Serious Infections9(5.4%)2(1.2%)#p<0.001 vs. Placebo. $Missing data were imputed by multiple imputation. +AEs with an incidence of ≥3% in any group were listed.FAS, full analysis set. SRI, SLE responder index. MI, missing data were imputed by multiple imputation. NRI, missing data were imputed as non-response. LOCF, missing data were imputed by last observation carry forward method. PGA, physician’s global assessment. SFI, SLE flare index. SS, safety set. TEAE, treatment-emergent adverse event. SAE, serious adverse event. SOC, system organ class.ConclusionThis phase 3 trial met the primary endpoint. Telitacicept 160 mg showed good clinical benefits and a favorable safety profile in SLE patients.Reference[1]Dhillon S. Telitacicept: First Approval. Drugs. 2021 Sep;81(14):1671-1675.AcknowledgementsThe patients and their families who participated in this clinical trial.Disclosure of InterestsLi Wang: None declared, JING LI: None declared, Dong Xu: None declared, Jianmin Fang Shareholder of: RemeGen Co., Ltd, Employee of: RemeGen Co., Ltd, Ronald van Vollenhoven: None declared, Fengchun Zhang: None declared.